Cross-cultural design. 7th International Conference, CCD 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: 7th International Conference, CCD 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Applications in mobile interaction, education, health, transport and cultural heritage : Part II, (2015) - Unknown
No abstract available